Perceptions of cruise travel during the COVID-19 pandemic: Market recovery strategies for cruise businesses in North America. (August 2021) - Pan, Tianyu; Shu, Fang; Kitterlin-Lynch, Miranda; Beckman, Eric
Abstract: The study aims to identify consumer perceptions of the cruise industry amid the COVID-19 pandemic and seeks to provide market recovery strategies for cruise businesses. The relationship between perceptions among cruise experience and COVID-19 financial status groups were explored. The results of analyses of data from 759 respondents indicated that travel constraints negatively influence behavioral intention through negativity bias. Further, perceived crisis management positively affects behavioral intention through attitude-trust. New consumers' behavioral intention is significantly affected by the negativity bias, and the perceived crisis management manipulates the trust of financial-affected consumers. Highlights: This study proposed market recovery strategies for cruise businesses during the COVID-19. This study combined and extended the leisure constraint theory and prospect theory in cruise tourism. A survey of a total of 759 new and repeat cruise tourists was conducted in this study. This study provides insightful tourists' perceptions and behavioral information, helping cruise businesses overcome challenges during COVID-19.